GENDER POLICY OF THE CATHOLIC CHURCH OF INDIA: A Contribution of the Indian Church for Women Empowerment - Kochuthara, Shaji George (Journal of Dharma, 2016)
The Gender Policy of the Catholic Church of India, released on 24 February 2010, is the first official gender policy, published by a Catholic Bishops' Conference in the universal Church. Though the Indian society and the Church still continue to be predominantly patriarchal, the Bishops' Conference took the courageous step to officially declare a policy for the empowerment of women, and opening doors for more creative roles in the Church. The initiative and work for this policy was undertaken by committed women and supported by others, including the bishops. Gender Policy is a good starting point for the empowerment of women in the Church and Society, and if implemented, it can become a model and tool for women empowerment in India. However, it has to be studied seriously and implemented with sincere commitment, especially by those in authority. Measures to make women aware of their rights in the Church and society are also needed.